The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.2174/138955706778993049
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into the Regulation of Liver Inflammation and Oxidative Stress

Abstract: Pro-inflammatory lipid mediators (i.e. eicosanoids), cytokines (i.e. TNF-alpha) and reactive oxygen species are targets of interest in the regulation of liver inflammation and oxidative stress. In the current review, we summarize recent advances in the pharmacological modulation of these pathways with especial emphasis on the participation of Kupffer cells, the liver resident macrophages and the cell type most directly related to the production of inflammatory mediators in this organ.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 127 publications
1
10
0
1
Order By: Relevance
“…Because of this, we expect that the liberated gold ions are most likely present as gold cyanide AuCN molecules, i.e. Au + , since it is well known that macrophages can release cyanide and regulate oxygen tension and pH-value in their immediate surroundings (Ferre and Claria 2006). The following chemical process is believed to take place:…”
Section: Discussionmentioning
confidence: 99%
“…Because of this, we expect that the liberated gold ions are most likely present as gold cyanide AuCN molecules, i.e. Au + , since it is well known that macrophages can release cyanide and regulate oxygen tension and pH-value in their immediate surroundings (Ferre and Claria 2006). The following chemical process is believed to take place:…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, KCs are not only relevant in HBV-and HCV-induced inflammation but also in the development of associated fibrosis and HCC. One study of KC depletion leading to attenuated liver injury (23) suggested an adverse net effect of liver macrophages, but the possible influence of macrophages will depend on their phenotypes and activation status.…”
Section: Macrophages Influence Liver Fibrosis and Cirrhosis And Cancermentioning
confidence: 99%
“…Oxidative stress and inflammation are known to be associated with liver injury and development of liver diseases (Ferre and Claria, 2006; Dasarathy, 2008). Liver cells respond to exposure to drugs, chemicals and xenobiotics by activating intrinsic defense mechanisms aimed at neutralizing the insult and repairing the damage.…”
Section: Introductionmentioning
confidence: 99%